2-Hydroxyglutarate in Cancer Cells - Ježek, Petr (Antioxidants & redox signaling, 2020)
Significance: Cancer cells are stabilized in an undifferentiated state similar to stem cells. This leads to profound modifications of their metabolism, which further modifies their genetics and epigenetics as malignancy progresses. Specific metabolites and enzymes may serve as clinical markers of cancer progression. Recent Advances: Both 2-hydroxyglutarate (2HG) enantiomers are associated with reprogrammed metabolism, in grade III/IV glioma, glioblastoma, and acute myeloid leukemia cells, and numerous other cancer types, while acting also in the cross talk of tumors with immune cells. 2HG contributes to specific alternations in cancer metabolism and developed oxidative stress, while also inducing decisions on the differentiation of naive T lymphocytes, and serves as a signal messenger in immune cells. Moreover, 2HG inhibits chromatin-modifying enzymes, namely 2-oxoglutarate-dependent dioxygenases, and interferes with hypoxia-inducible factor (HIF) transcriptome reprogramming and mammalian target of rapamycin (mTOR) pathway, thus dysregulating gene expression and further promoting cancerogenesis. Critical Issues: Typically, heterozygous mutations within the active sites of isocitrate dehydrogenase isoform 1 (IDH1)R132H and mitochondrial isocitrate dehydrogenase isoform 2 (IDH2)R140Q provide cells with millimolar r-2-hydroxyglutarate (r-2HG) concentrations, whereas side activities of lactate and malate dehydrogenase form submillimolar s-2-hydroxyglutarate (s-2HG). However, even wild-type IDH1 and IDH2, notably under shifts toward reductive carboxylation glutaminolysis or changes in other enzymes, lead to "intermediate" 0.01-0.1 mM 2HG levels, for example, in breast carcinoma compared with 10-8M in noncancer cells. Future Directions: Uncovering further molecular metabolism details specific for given cancer cell types and sequence-specific epigenetic alternations will lead to the design of diagnostic approaches, not only for predicting patients' prognosis or uncovering metastases and tumor remissions but also for early diagnostics.
Keywords: isocitrátdehydrogenasa; Glutarates; Disease Progression; lidé; náchylnost k nemoci; Immunomodulation; Energy Metabolism; Oxidation-Reduction; Mutation; Neoplastic Stem Cells; energetický metabolismus; glutaráty; Signal Transduction; progrese nemoci; Humans; mutace; Gene Expression Regulation, Neoplastic; signální transdukce; epigeneze genetická; nádory; zvířata; nádorové kmenové buňky; Epigenesis, Genetic; oxidace-redukce; Animals; regulace genové exprese u nádorů; Disease Susceptibility; imunomodulace; Isocitrate Dehydrogenase; Neoplasms